I4 Epidemiology of huntington's disease in cyprus: in search of a founder effect. (13th September 2016) - Demetriou, Christiana A; Salafori, Chryso; Christou, Yiolanda; Heraclides, Alexandros; Zamba-Papanicolaou, Eleni
Abstract : Background and aim: Huntington's disease (HD) is a fully penetrant, mainly adult-onset, autosomal dominant disorder. HD is caused by repetitions of the triplet CAG in chr 4 (4p16.3), which are pathogenic if ≥36. Globally, the prevalence is highest among populations of western European descent. In more isolated populations the origin of HD is usually a result of founder effects, which can give rise to higher than normal prevalence as well as geographical clustering. Our aim was to conduct a detailed epidemiological investigation of HD in the island of Cyprus. Methods: All registered Greek Cypriot HD patients were analysed from 1984 onwards. Detailed pedigrees and maps, examining the geographic distribution of the disorder, were constructed. Results: Eighty confirmed cases of HD were identified since 1984 belonging to 16 independent families concentrated in a small cluster spanning the Famagusta and Larnaca districts. Three cases were juvenile HD (JHD). In 2015 the prevalence was 7.61/100, 000, and the incidence 0.12/100.000. The crude average annual incidence from 1984 to 2015 was 0.26/100000 (95% CI: 0.20–0.34). The 5-, 10-, and 15-year survival probability was 85.2%, 63.0% and 40.7% respectively, with average disease duration of 12.2 years, excluding JHD. The average age at onset was 44.2 years and the average number of CAG repeats in the mutant allele was 44. Paternal inheritance had in general a more adverse disease profile. The age at onset was found to decrease significantly over decades and with increasing number of CAG repeats. Conclusions: Cyprus has HD prevalence and incidence higher than other southern European countries, making the possibility for a founder effect very likely. The geographical clustering observed points to a very likely western European origin of the disease, given the strong presence of such populations in the affected region during the middle-ages. Disease characteristics such as the median number of CAG repeats, age at onset and disease duration are comparable to other countries.